THE CHARACTERISATION AND COMBUSTION OF SOUTH AMERICAN COALS - Barranco Melendez, Richelieu (2001)
On an international basis, coal is used extensively for power generation and this is likely to remain the case well into this century. Although many standard tests are currently used to assess and select coals for combustion purposes, these have proven to be unable to predict coal burnout behaviour. For a power station based on coal combustion, a clear knowledge and understanding of the coals offered in the market is essential to achieve optimum conversions and to meet environmental constraints. There is, therefore, a need to develop suitable and efficient methods and techniques to characterise coals so that the combustion plant performance can be predicted more effectively.